Caregiver Characteristics Associated With Quality of Cardiac Compressions on an Adult Mannequin With Real-Time Visual Feedback: A Simulation-Based Multicenter Study. Issue 2 (April 2020) - Kessler, David O.; Lemke, Daniel S.; Jani, Priti; Dewan, Maya L.; Moore-Clingenpeel, Melissa; Chang, Todd P.; Pirie, Jonathan; Lovett, Marlina E.; Harwayne-Gidansky, Ilana; Wolfe, Heather A.
Abstract : Introduction: Chest compression (CC) quality directly impacts cardiac arrest outcomes. Provider body type can influence the quality of cardiopulmonary resuscitation (CPR); however, the magnitude of this impact while using visual feedback is not well described. The aim of the study was to determine the association between provider anthropometric variables on fatigue and CC adherence to 2015 American Heart Association CPR while receiving visual feedback. Methods: This was a planned secondary analysis of healthcare professionals from multiple hospitals performing continuous CC for 2 minutes on an adult CPR mannequin with dynamic visual feedback. Main outcome measures include compression data (depth, rate, and lean) evaluated in 30-second epochs to explore performance fatigue. Multivariable models examined the relationship of provider anthropometrics to CC quality. Binomial mixed effects models were used to characterize fatigue by examining performance for 4 epochs. Results: Three hundred seventy-seven 2-minute CC episodes were analyzed. Extreme (low and high) BMI and weight are associated with poorer CC. Larger size (height, weight, and BMI) is associated with better depth but worse lean compliance. Performance fatigued for all providers for 2 minutes, but shorter, lighter weight, female participants had the greatest decline. On multivariable analysis, rate compliance did not deteriorate regardless of provider anthropometrics. Conclusions: Anthropometrics impact provider CC quality. Despite visual feedback, variable effects are seen on compression depth, rate, recoil, and fatigue depending on the provider sex, weight, and BMI. The 2-minute interval for changing chest compressors should be reconsidered based on individual provider characteristics and risk of fatigue's impact on high-quality CPR. Abstract : Supplemental digital content is available in the text.